Conservative Management of Divergent Dislocation of the 2nd–5th Carpometacarpal Joints - AM, Abdoul Wahab; Chaibou, B; Allamine, A; Souna, BS (Nigerian Journal of Orthopaedics and Trauma, 2020)
Carpo-metacarpal dislocations are rare lesions, the authors report a case of convergent carpo-metacarpal dislocation of the last four fingers, received urgently and treated by reduction and plastered cuff, it was for us a therapeutic alternative, patient had refused surgical treatment which has been indicated, it is essentially a reduction more pinning. The immobilization lasted one month then a physiotherapy of functional rehabilitation of the removal of the plaster was also carried out. The functional result was satisfactory and professional reintegration was successfully completed.